Dr. Sheila Singh: The Complexity of Brain Tumours - Ho, Bernard; Ostrovski, Ilia; Sorouri, Kimia (The Meducator, 2013)
The Meducator recently sat down with Dr. Sheila Singh, Associate Professor and scientist at the Stem Cell and Cancer Research Institute at McMaster University, to discuss her ground-breaking research on brain tumour-initiating cells and her hopes for future generations of scientists. Dr. Singh explained to us how she was able to make her discovery and why the science of tumours is such an intricate one. She also shared her insights about the long road ahead for clinicianscientists and described why students should take their time with their careers.